Developing engaging STEAM-geometry activities: Fostering mathematical creativity through the engineering design process using Indonesian cuisine context - Pramasdyahsari, Agnita Siska; Rubowo, Maya Rini; Nindita, Velma; Astutik, Iin Dwi; Pant, Binod Prasad; Dahal, Niroj; Luitel, Bal Chandra (IKIP Siliwangi and I-MES, 2025)
Enhancing mathematical creativity requires more learning activities that foster creative thinking. However, teachers need more resources and activities to nurture students' creativity in mathematics effectively. Therefore, this study aimed to design STEAM-based geometry activities using the Engineering Design Process (EDP) to explore how such projects can enhance students' mathematical creativity. In this study, creativity focuses on how students use geometric principles to design Wingko Babat as an Indonesian cuisine, making culturally meaningful connections and solving design challenges. The study involved research and development using the analysis, design, development, implementation, and evaluation (ADDIE) model, continuing with a descriptive qualitative approach. The activities designed for the STEAM-Geometry projects allow students to think creatively and elaborate on the engineering design process. Through expert reviews that involved multiple educators, the design activities on the STEAM-Geometry project are reliable and valid. The findings show that the EDP on Geometry project enables students to think creatively. The findings imply that teaching geometry can develop the students' mathematical creativity through the engineering design process in STEAM activities. Furthermore, it indicates that the design activities encompass more than just understanding geometry; they also nurture creativity by applying STEAM principles in the engineering design process. Integrating STEAM principles within culturally meaningful, geometry-based tasks enhances students' critical thinking, creativity, collaboration, and real-world problem-solving skills, preparing them to tackle complex challenges beyond the scope of mathematics.